FadA antigen of Fusobacterium nucleatum: implications for ceRNA network in colorectal cancer and adenomatous polyps progression - Sama Rezasoltani; Elahe Shams; Moein Piroozkhah; Yaser Aidi; Mehdi Azizmohammad Looha; Parmida Bagheri; Roudabeh Behzadi Andouhjerdi; Amir Sadeghi; Leili Rejali; Ehsan Nazemalhosseini-Mojarad (Discover Oncology)
Abstract Introduction Colorectal cancer (CRC) is the second most common cause of cancer-related deaths globally. The gut microbiota, along with adenomatous polyps (AP), has emerged as a plausible contributor to CRC progression. This study aimed to scrutinize the impact of the FadA antigen derived from Fusobacterium nucleatum on the expression levels of the ANXA2 ceRNA network and assess its relevance to CRC advancement. Material and methods The functions of ANXA2 and LINC00460 in CRC have been partially clarified. According to our previous study to identify shared MicroRNA-Interaction-Targets (MITs) between ANXA2 and LINC00460, TargetScanHuman (V7.2) and miRDB databases have been used respectively. The Bioinformatics and Evolutionary Genomics web tool was employed to intersect the sets of shared microRNAs and their common targets. Then, the ANXA2 ceRNA network was constructed. Subsequently, the mRNA, miRNA, and lncRNA expression levels were examined in intestinal biopsy specimens from 30 healthy controls, 30 Adenoma patients, and 30 cases of CRC stage I using qRT-PCR. Results Elevated expression levels of FadA, ANXA2, hsa-let-7a-2, and LINC00460 were observed in CRC specimens, followed by AP cases, in comparison to samples from normal individuals. Application of the Spearman test revealed a strong and significant correlation between FadA and LINC00460 (rS = 0.9311, p < 0.0001). Also, the functional analysis of ANXA2 revealed its impact on CRC progression through JAK-STAT and Hippo signaling pathways. Conclusion FadA appears to potentiate CRC progression by inducing the upregulation of LINC00460, consequently leading to the hyperexpression of ANXA2 through the ceRNA network.